Tax revenues of the Berehove territorial community budget: a structural-dynamic analysis (2021–2025) - Gabriella Loskorikh; Лоскоріх Габріелла; Loszkorih Gabriella; Veronika Hanusych; Hanuszics Veronika; Ганусич Вероніка; Oksana Perchi; Pércsi Oxána; Перчі Оксана (NGO "Research and Educational Innovation Center of Social Transformations", 2026)
Abstract. The sustainability of the revenue base of local budgets during wartime largely depends on the stability of tax revenues and the ability of communities to adapt their tax base to changes in economic activity. The purpose of this study is to conduct a structural-dynamic analysis of tax revenues of the Berehove Territorial Community budget in 2021–2025 and to substantiate directions for strengthening and diversifying the tax base. The Berehove Territorial Community, located in Ukraine’s western border region, is characterized by a specific sectoral structure of entrepreneurship, a significant role of small and medium-sized enterprises, and active cross-border economic linkages. The study employs an empirical analysis of the community’s budget execution indicators, with a focus on changes in the structure of tax revenues and the role of different categories of taxpayers. The analysis proceeds from the hypothesis that the growth of tax revenues during the wartime period is uneven across tax groups and is accompanied by a transformation in the relative fiscal contributions of individuals and legal entities. The methodological framework includes structural-dynamic analysis and factor decomposition of the contribution of major tax groups to changes in total tax revenues. The results reveal the dominance of taxes on income, profits, and capital gains, alongside an increasing contribution of local taxes and fees as well as internal taxes on goods and services. It is demonstrated that the main increase in tax revenues in 2021–2024 was generated primarily by income-related taxes and local taxes and fees, while other components had a limited impact. Changes in the structure of taxpayers are also identified: in 2023–2024, the share of individuals in the total amount of taxes paid increased, whereas in 2024–2025 the growth of revenues was predominantly ensured by legal entities. The theoretical significance of the study lies in the advancement of approaches to assessing the sustainability of a community’s tax base through the combined application of structural-dynamic and factor analysis. The practical significance is reflected in the possibility of using the results to refine local tax policy priorities and to support the diversification of the revenue base. A limitation of the study is the use of 2025 data covering only nine months; further research should refine the conclusions based on full-year data for 2025 and provide a more detailed breakdown by specific taxes and types of economic activity.

Резюме. Стійкість доходної бази місцевих бюджетів у воєнний період значною мірою визначається стабільністю податкових надходжень і здатністю громад адаптувати податкову базу до змін економічної активності. Метою дослідження є здійснення структурно-динамічного аналізу податкових надходжень бюджету Берегівської територіальної громади у 2021–2025 рр. і обґрунтування напрямів зміцнення та диверсифікації податкової бази. Берегівська територіальна громада, розташована в західному прикордонному регіоні України, характеризується специфічною галузево-секторальною структурою підприємницького сектору, значною роллю малого й середнього бізнесу та активними транскордонними економічними зв’язками. Дослідження виконано як емпіричний аналіз показників виконання бюджету громади з фокусом на зміні структури податкових надходжень і ролі платників податків. Вихідним припущенням є нерівномірність внеску окремих груп податків у приріст доходів та трансформація співвідношення фіскального внеску фізичних і юридичних осіб у воєнних умовах. Застосовано структурно-динамічний аналіз та факторну декомпозицію внеску основних груп податків у зміну загального обсягу податкових надходжень. У результаті встановлено домінування податків на доходи, прибуток і приріст капіталу, зростання внеску місцевих податків і зборів й внутрішніх податків на товари та послуги. Доведено, що основний приріст податкових надходжень у 2021–2024 рр. сформовано переважно за рахунок податків на доходи та місцевих податків і зборів, тоді як інші компоненти мали обмежений вплив. Охарактеризовано зміни у структурі платників: у 2023–2024 рр. зросла частка фізичних осіб у загальній сумі сплачених податків, натомість у 2024–2025 рр. приріст надходжень переважно забезпечено юридичними особами. Теоретичне значення полягає у поглибленні підходів до оцінювання стійкості податкової бази громади на основі поєднання структурно-динамічного та факторного аналізу. Практичне значення полягає у можливості використання результатів для уточнення пріоритетів місцевої податкової політики та диверсифікації доходної бази. Обмеженням є використання даних за 2025 рік у форматі 9 місяців; перспективним є уточнення висновків за підсумками повного 2025 року та деталізація аналізу за окремими податками і видами економічної діяльності.
Податкові надходження бюджету Берегівської територіальної громади: структурно-динамічний аналіз (2021–2025)
Весь випуск: https://reicst.com.ua/pmt/issue/view/issue_23_2026
Keywords: tax revenues; local budget; fiscal decentralization; martial law; structural-dynamic analysis